Induction of apoptosis by synthetic ceramide analogues in the human keratinocyte cell line HaCaT - Bektas, Meryem; Dullin, Y.; Wieder, T.; Kolter, T.; Sandhoff, K.; Brossmer, Reinhard; Ihrig, Petra; Orfanos, C. E.; Geilen, C. C. (Experimental dermatology, 1998)
Abstract: In contrast to extracellular, long chain ceramides which comprise a structural component of the epidermal water barrier, intracellular ceramides originating from sphingomyelin hydrolysis have been shown to inhibit proliferation and to induce apoptosis in different cell populations. To further elucidate the possible role of intracellular ceramides in human epidermis, two new cell-permeable ceramide analogues, N-thioacetylsphingosine (C2-Cer=S) and 4-dodecanoylamino-decan-5-ol (FS-5), were synthesized and tested for their ability to suppress cell growth and to induce apoptosis in immortalized human keratinocytes. It was shown that the well-investigated ceramide analogue N-acetylsphingosine (C2-Cer=O), as well as the new compound C2-Cer=S inhibited proliferation of HaCaT cells with half-inhibitory concentrations (IC50) of 20 μg/ml and 10 μg/ml, respectively, whereas FS-5 has been potent with an IC50>40 μg/ml. Overall, all three ceramide analogues induced apoptosis in HaCaT cells as assessed by DNA-fragmentation using ELISA technique and in situ nick end labelling, thereby confirming the importance of ceramide signalling in keratinocytes.
Elektronische Reproduktion der Druck-Ausgabe 4. Mai 2007
Gesehen am 26.06.2024